On the theory of stability of matrix differential equations - Lila, D. M.; Martynyuk, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish the conditions of asymptotic stability of a linear system of matrix differential equations with quasiperiodic coefficients on the basis of constructive application of the principle of comparison with a Lyapunov matrix-valued function.